The Person-Centred Care Index Revisited - Sanjay Kalra; Sourabh Sharma; Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2026)
Person-centered care can be measured and monitored by using validated tools such as the Person-centered care Index (PCI). Simpler and shorter versions of such indices may help in enhancing their appeal, and expanding their usage across health care settings. We propose a visual, simplified tabular, and brief textual version of the PCI. These alternatives can complement the original tool, and serve as user-friendly teaching tools. Keywords: Biopsychosocial model, chronic care model, patient centered care, person-centered care.